INNOVATION IN CASCARA TEA FORMULATION TO INCREASE CONSUMER ACCEPTANCE - Khairul Nanda Munthe; Ika Ucha Pradifta Rangkuti; Rafael Remit Winardi (RADJA PUBLIKA, 2026)
The utilization of coffee husk waste (cascara) as a functional drink still faces obstacles due to low consumer acceptance because of its less favored taste and aroma. This study aimed to determine the effect of cascara tea formulation with the addition of ginger and roselle on physicochemical quality and consumer acceptance. The study used a Completely Randomized Design (CRD) non-factorial with four treatments and three replications, namely C0 (100% cascara), C1 (50% cascara + 50% ginger), C2 (50% cascara + 50% roselle), and C3 (40% cascara + 30% ginger + 30% roselle). Parameters observed included moisture content, pH, organoleptic characteristics (aroma, color, taste), and total phenols in the best treatment. The results showed that the formulation had a significant effect on pH (P<0.05), aroma, and taste (P<0.01), but no significant effect on moisture content and color (P>0.05).. The best treatment was obtained in C3 with an aroma score of 3.84 and a color score of 4.50. Analysis of total phenols in the best treatment showed a value of 44.39%. The combination of cascara, ginger, and rosella can improve consumer acceptance and produce an herbal drink that has the potential as a source of natural antioxidants.